Tunability Response in Exponentially Graded Ferroelectrics: A Transverse Ising Model Approach (2011)
Cálculo de la función dieléctrica relativa para un sistema ferroeléctrico con gradaciones que consiste en una estructura alineada (en capas), utilizando el Modelo de Ising Transversal / Abstract: Calculation of the relative dielectric function for a Ferroelectric Graded System consisting in aligned (layered) structure, by using the Transverse Ising Model